PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL SEBAGAI PENDORONG INOVASI DAN INDUSTRIALISASI BERBASIS KEBERLANJUTAN - Carina Budi Siswani; Roberth Kurniawan Ruslak Hammar (Fakultas Hukum, Universitas Caritas Indonesia, 2025)
This article examines the position of intellectual property rights (IPR) within the national legal framework as a mechanism to strengthen innovation and accelerate the process of industrialization aligned with the principles of sustainability. The discussion focuses on reinforcing the legal protection framework for creative works and technological discoveries in relation to the achievement of Sustainable Development Goal 9 (SDG 9), which emphasizes the importance of infrastructure development, inclusive industrial growth, and the enhancement of technological capacity. This study adopts a normative legal approach through literature review of statutory regulations, international legal instruments, and national policy frameworks from various jurisdictions. The findings reveal that the conceptualization of IPR must be broadened—from a solely protective mechanism to an integral component of the legal infrastructure for development. Institutional disparities, structural barriers, and limitations in legal access continue to obstruct the strategic role of IPR in many developing countries, including Indonesia. Accordingly, there is a pressing need for policy frameworks that are open, equitable in access, and responsive to the needs of informal-sector innovators. Legal protection for IPR must be coupled with principles of benefit-sharing and distributive justice in the governance of innovation outputs. These findings suggest the urgency of redesigning the national IPR system to substantively support sustainable development objectives.